2022
DOI: 10.3390/ma16010025
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Mannitol Granules Produced by Spray Drying and Sacrificial Templating

Abstract: In pharmaceutical applications, the porous particles of organic compounds can improve the efficiency of drug delivery, for example into the pulmonary system. We report on the successful preparation of macroporous spherical granules of mannitol using a spray-drying process using polystyrene (PS) beads of ~340 nm diameter as a sacrificial templating agent. An FDA-approved solvent (ethyl acetate) was used to dissolve the PS beads. A combination of infrared spectroscopy and thermogravimetry analysis proved the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…162 Alternatively, templating agents, such as spherical beads, which are removable after drying, can be used. 163,164…”
Section: Reviewmentioning
confidence: 99%
“…162 Alternatively, templating agents, such as spherical beads, which are removable after drying, can be used. 163,164…”
Section: Reviewmentioning
confidence: 99%
“…However, further studies are required to assess the influence of the pH, which is acidic in tumors on the desorption of the alkaloids from the delivery nanoplatform as well as the cytotoxic activity against normal cell lines, before proceeding to in vivo preclinical studies. Other papers deal with various syntheses of nano-and micro-sized particulate systems for biopharmaceutical applications [3][4][5][6][7]. V. Mikelashvili, L. Almasy, et al [3] presented the characterization of citric acid-capped magnetite nanoparticles synthesized using an electrohydraulic discharge treatment.…”
mentioning
confidence: 99%
“…At a nanoparticle concentration of 25 µg/mL, reductions with respect to untreated controls of biofilm mean thickness and biomass of 85% and 65%, respectively, were evidenced for both biofilms through confocal scanning laser microscopy analysis using COMSTAT software. M. Valentin, B. Vertruyen, et al [5] reported the successful preparation of spherical macroporous mannitol (M) granules with diameters of about 2-3 µm via a spray drying technique using polystyrene (PS) beads as a sacrificial template and an FDA-approved ethyl acetate solvent as an etching agent. The influence of the M/PS mass ratio on the etching efficiency reflected in the material porosity was studied and the authors also investigated how the homogeneity of the porosity distribution was affected by upscaling the synthesis process from lab-scale to pilot-scale conditions.…”
mentioning
confidence: 99%